2012
DOI: 10.1074/jbc.m111.300681
|View full text |Cite
|
Sign up to set email alerts
|

Ringo/Cyclin-dependent Kinase and Mitogen-activated Protein Kinase Signaling Pathways Regulate the Activity of the Cell Fate Determinant Musashi to Promote Cell Cycle Re-entry in Xenopus Oocytes

Abstract: Background:The mechanisms that regulate the activity of the mRNA translational regulator, Musashi, are unknown. Results: Musashi is activated by Ringo/cyclin-dependent kinase and MAP kinase signaling. Conclusion: Musashi-directed mRNA translation induces MAP kinase signaling and establishes a positive feedback loop to amplify Musashi activity. Significance: Musashi activation to promote translation of target mRNAs presents a potential target for the control of pathological cell cycle progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 48 publications
2
62
0
Order By: Relevance
“…In this context, PARN is thought to exert a dominant effect and thereby override GLD2 activity to maintain short poly(A) tails and translational dormancy. Upon progesterone stimulation, CPEB1 undergoes phosphorylation of Ser-174, which triggers expulsion of PARN from the complex and leads to the unopposed action of GLD2 and consequent extension of poly(A) tails of CPE-regulated mRNAs (23). We see a similar co-association of Musashi with both GLD2 and PARN in immature oocytes.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In this context, PARN is thought to exert a dominant effect and thereby override GLD2 activity to maintain short poly(A) tails and translational dormancy. Upon progesterone stimulation, CPEB1 undergoes phosphorylation of Ser-174, which triggers expulsion of PARN from the complex and leads to the unopposed action of GLD2 and consequent extension of poly(A) tails of CPE-regulated mRNAs (23). We see a similar co-association of Musashi with both GLD2 and PARN in immature oocytes.…”
Section: Discussionsupporting
confidence: 59%
“…Ringo then activates free cyclin-dependent kinase subunits, triggering phosphorylation of several targets, including Musashi (23). Musashi phosphorylation triggers the cytoplasmic polyadenylation and translation of several target mRNAs, including those encoding Mos, cyclin B5, and Nrp1A/B (Musashi-1) prior to GVBD (10,(23)(24)(25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…mRNAs containing MBEs are bound by the Musashi protein, contain short poly(A) tails, and are translationally repressed in oocytes by an unknown mechanism. In response to progesterone and oocyte maturation, Musashi is phosphorylated, and the protein directs the polyadenylation of MBE-containing mRNAs, through the recruitment and/or activation of a poly(A) polymerase (Cragle and MacNicol 2014b; Arumugam et al 2012). …”
Section: 5 Translational Control Mechanisms Operating During Xenopumentioning
confidence: 99%
“…The presence of Musashi protein in immature stage VI oocytes suggested that Musashi must undergo a functional switch in response to progesterone to promote MBE-dependent early class polyadenylation and translational activation. Phosphorylation of Musashi1 is initially dependent upon Ringo/CDK activity and is subsequently augmented by MAP kinase signaling (Arumugam et al 2012b). Mutational disruption of these sites abrogates the ability of Musashi1 to mediate MBEdependent polyadenylation and translational activation.…”
Section: Cpe-independent Mrna Translational Regulationmentioning
confidence: 99%